Studi Fenomenologi Online Self Disclosure melalui Instagram Story - Arkani Yz-zahra, Fayaretharatri; Hasfi, Nurul (Interaksi Online, 2019)
This study aims to understand how users experience when doing self disclosure in Instagram Story. This study is motivated by the emergence of the phenomenon of social media that is widely used by the public, namely Instagram, whose presence makes self disclosure that was previously done face-to-face now changed through social media. This study was conducted with a qualitative descriptive method with a phenomenological approach. The main theory used in this study is the Self-Disclosure Theory. Data collection techniques were carried out by in-depth interviews with 7 informants. This study found that the motivation of users to reveal themselves found in this study is to built image of themselves, to share & find solutions, as a storage, to seek attention, and to exist. The other things that found in this study related to self disclosure are identity, themes, personal information, and effect. The users will open their identities when expressing positive things about themselves and will cover their identities when expressing negative things. The themes expressed by users vary according to the perceptions of the personal information of each user. Users have their own restrictions on personal information disclosed. The effect that is obtained when revealing oneself is that the user feels relieved and happy after expressing their self.